Exploring the use of Edmodo group discussion feature as collaborative learning approach - Noor Azlinda, Zainal Abidin; Aisyah Hanum, Abu Bakar; Zuraina, Ali (Global Business Entrepreneurship, 2018)
Collaborative learning approach using Web 2.0 is used in teaching and learning nowadays. Group projects are done virtually in ensuring collaborative approach is applied. By doing this, it engaged students’ participation and encouraged students’ interaction. Due to its flexibility, time and also venue are decided by the group members based on their comfort. This paper aims to study previous research done in the use of Edmodo in teaching and learning and how collaborative learning approach is embedded. Not only that it also explores other studies carried out on group discussion via Edmodo in completing the work assigned.